Buzzeringuistics: Decoding Digital Propaganda through Cyberpragmatics - Arkin Haris (UIN Salatiga, 2026)
This study examines how political buzzer discourse on social media constructs persuasion through the interaction of speech acts, cyberpragmatic functions, and digital politeness strategies. Focusing on competing hashtag discourses IndonesiaEmas and IndonesiaCemas on X, the study adopts a descriptive qualitative approach to explore how meaning, intention, and ideological positioning are pragmatically negotiated in online political communication. The data consist of selected user-generated comments representing polarized political engagement and were analyzed using speech act theory and cyberpragmatics. The findings indicate that assertive speech acts dominate buzzer discourse by presenting evaluative judgments and ideological claims as established realities, reinforced by expressive and directive acts that mobilize emotions and encourage audience alignment. The persuasive force of these utterances is strengthened through five cyberpragmatic functions, namely contextual saturation, non-verbal compensation, cyber-aggression, high inferential load, and algorithmic relevance optimization, reflecting how digital affordances shape interpretation and intensify pragmatic effects. The study also identifies three strategic patterns in digital politeness management, namely legitimization, delegitimization, and mitigation, which construct in-group solidarity and regulate face-threatening acts in polarized discourse. The findings show that buzzer communication operates as a systematic form of performative political discourse. The study proposes Buzzeringuistics as an integrative analytical framework that combines cyberpragmatics, speech act analysis, and critical perspectives to explain digitally mediated political persuasion.